The timed failures - stability model for CSP - Reed, G; Roscoe, A (Elsevier, 1999)
We present a mathematical model which is the most abstract allowing (i) a fully compositional semantics for timed CSP and (ii) a natural abstraction map into the standard failures/divergences model of untimed CSP. We discuss in detail the construction and properties of this model, and explore the variety of nondeterministic behaviour it encompasses. We argue that, at least in some sense, this model is definitive for timed CSP.